Translation as a Provider of Models of Sociological Discourse in Nusantara - Smith, Brian (TTR)

(untitled) (Association canadienne de traductologie, 1997)
AbstractTranslation as a Provider of Models of Sociological Discourse in Nusantara — The social sciences have seen rapid growth both as academic subjects and as instruments of national development in the Malay language nations of SE Asia: Brunei Darussalam, Indonesia and Malaysia. The particular nature of social science terminology and discourse has presented special problems for translators of social science texts, who have been at the frontiers of language creation as national language texts have been increasingly used at all levels of education in Indonesia and Malaysia.In Indonesia, where higher education had been Indonesian-medium after independence, the first social science texts to be translated were from Dutch, but, following the departure of the Dutch, extensive American support to social science education by the USA from the 1960s led to a new wave of texts translated from English. In Malaysia the decision to introduce Malay-medium higher education created a need for translations of key texts from English. In Brunei Darussalam, while higher education is English-medium, Malay-medium university students have found it necessary to translate English social science material to succeed in their learning.While the three countries have an agreement to standardise terminology and discourse, social science language has to some extent diverged. Meanwhile a serious shortage of qualified translators has hampered the production of adequate and sufficient translations.This paper discusses (1) the issues of "transparency" and "invisibility" in providing Indonesian and Malay target texts and (2) the feasibility of "domesticating" concepts and methodologies and providing recipient language texts which are usable and developmental.